Platforms of inequality: gender dynamics of digital labour in Africa - Anwar, Mohammad Amir (Gender and development, 2022)
Paid work and gender equality are key elements of international development discourse on women's economic empowerment. New digital technologies are considered to generate paid work opportunities for the marginalised groups in Africa, particularly women. The rise of the platform economy (work digitally mediated via platforms), for example, is framed as a panacea to poverty and informality among women. Yet the evidence remains anecdotal so far. Drawing on the author's empirical research conducted between 2015 and 2021 on two kinds of digital labour (remote and place-based work) in Africa, the paper examines the job-quality outcomes among women gig workers in five African countries. The paper highlights new gender-based inequalities on platforms and the ways in which women cope with such outcomes. In particular, it outlines economic insecurities, discrimination at work, high work intensity and adverse physical and psychological impacts among women workers on platforms. It advances the cause for women's labour rights and offers policy recommendations for a gender-equitable platform economy.